AabHLH112, a bHLH transcription factor, positively regulates sesquiterpenes biosynthesis in Artemisia annua - Xiang, Lien; He, Ping; Shu, Guoping; Yuan, Mingyuan; Wen, Mengling; Lan, Xiaozhong; Liao, Zhihua; Tang, Yueli (Frontiers in Plant Science, 2022)
The bHLH transcription factors play important roles in the regulation of plant growth, development, and secondary metabolism. β-Caryophyllene, epi-cedrol and β-farnesene, three kinds of sesquiterpenes mainly found in plants, are widely used as spice in the food industry and biological pesticides in agricultural production. Furthermore, they also have a significant value in the pharmaceutical industry. However, there is currently a lack of knowledge on the function of bHLH family TFs in β-caryophyllene, epi-cedrol and β-farnesene biosynthesis. Here, we found that AabHLH112 transcription factor had a novel function to positively regulate β-carophyllene, epi-cedrol and β-farnesene biosynthesis in A. annua. Exogenous MeJA enhanced the expression of AabHLH112 and genes of β-caryophyllene synthase(CPS), epi-cedrol synthase(ECS) and β-farnesene synthase(BFS), as well as sesquiterpenes content. Dual-LUC assay showed the activation of AaCPS, AaECS and AaBFS promoters were enhanced by AabHLH112. Yeast one-hybrid assay showed AabHLH112 could bind to the G-box (CANNTG) cis-element in promoters of both AaCPS and AaECS. In addition, overexpression of AabHLH112 in A. annua significantly elevated the expression levels of AaCPS, AaECS and AaBFS as well as the contents of β-caryophyllene, epi-cedrol and β-farnesene, while suppressing AabHLH112 expression by RNAi reduced the expression of the three genes and the contents of the three sesquiterpenes. These results suggested that AabHLH112 is a positive regulator of β-caryophyllene, epi-cedrol and β-farnesene biosynthesis in A. annua.